Confidence at work : get it, feel it, keep it - Taylor, Ros (KoganPage, 2011)
Teaches the reader the secrets of charisma. This title includes 20 case studies of successful people from all walks of life and professions, interviews with headhunters to find out what they look for in an ideal employee and other essential advice to help you become a sellable commodity